Individual muscle contributions to hip joint-contact forces during walking in unilateral transfemoral amputees with osseointegrated prostheses. Issue 14 (17th July 2020) - Harandi, Vahidreza Jafari; Ackland, David Charles; Haddara, Raneem; Cofré Lizama, L. Eduardo; Graf, Mark; Galea, Mary Pauline; Lee, Peter Vee Sin
Abstract: Direct skeletal attachment of prostheses in transfemoral amputees circumvents skin-interface complications associated with conventional sockets; however, joint pain and musculoskeletal disease is known to occur postoperatively. This study quantified hip contact forces and the roles of individual muscles in producing hip contact forces during walking in transfemoral amputees with osseointegrated prostheses. Musculoskeletal models were developed for four transfemoral amputees. Gluteus maximus and gluteus medius were the major contributors to the hip contact forces, and the intact limb hip muscles demonstrated greater contributions to hip contact forces than those of the residual limb. The findings may be useful for mitigating walking asymmetry.